Identity (Including Collective Identity): The History of Reflection, Research Scope and Overview of Definitions (Politeja, 2020)
Identity has remained a popular concept for many decades, being widely used in scientific research. This reflects not only the importance of the phenomena standing behind this notion, but also wide and deep changes accompanying the transition of societies from industrial to post-industrial, late modern, post-modern, network or information society. Regardless of the disputes about the nature of the new era, researchers agree that identities, including collective identities, play a key role in it, and the fight for the recognition of individual and social actors is an extremely important element of contemporary social processes and relations. The article presents a brief description of the most important points in the debate on identity, concerning its meaning, the subjects of identity, the dimensions of identity and the forms of its manifestations in social reality.